Reject water management at wastewater plants in Luleå - Tissot, François (2009)
The following study was conducted during the winter-spring 2009 at two wastewater treatment plants of the Luleå Kommun: Råneå and Uddebo. Several points were studied. For the Råneå plant, the aim of this work was to spot and solve the problem that was disturbing the functioning of the plant and altering the quality of the water rejected in the river. It turned out that a loop in the circulation of the reject water coming from the centrifuge led the way to a very high polymer concentration in the water going back to the entrance of the plant, which seemed to be the disturbing parameter. For the Uddebo plant the aim was to compare the performance of a new dewatering device – a press – to that of the centrifuge. It was found that the press was much more efficient than the centrifuge, using only 0,11kW to produce one kg of Total Solids (TS), while the centrifuge used 0,72kW to produce the same amount. An investigation about the feasibility of a full scale Freezing-Thawing step was also conducted at the Uddebo plant. It included working on the means to improve the process, in terms of dewatering,spreading, storing and harvesting of the sludge. A proposition of "Piled Up boxes" allowing a very flexible storage and Freezing-Thawing of the sludge was made at the end of the report. Validerat; 20101217 (root)